PENERAPAN CORETAX DALAM PEMENUHAN KEWAJIBAN PAJAK PENGHASILAN PASAL 15 PT YTA OLEH KKP GARFILD POSUMAH - Hanifa Aqil; Handini, Yuslinda Dwi (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2025)
The Directorate General of Taxes has introduced a new reform in the tax administration system called Coretax. This system integrates all core tax administration processes, including taxpayer registration, tax return filing, payment, audit, and tax collection for all types of tax objects in Indonesia, including Income Tax Article 15. Coretax represents one of the government’s efforts to improve the efficiency of tax governance. The purpose of this Internship Program is to understand the implementation of Coretax in fulfilling the Income Tax Article 15 obligations of PT YTA, facilitated by KKP Garfild Posumah. The data used in this Final Report consists of quantitative data obtained from the calculation, withholding, payment, and reporting of Income Tax Article 15, as well as qualitative data obtained through observations and interviews with the management and staff of KKP Garfild Posumah, along with secondary data from processed sources. The findings show that the implementation of Coretax in fulfilling the Income Tax Article 15 obligations of PT YTA involves several stages. The first stage is calculating Article 15 tax on domestic shipping based on input tax invoices received by PT YTA using a rate of 1.2% of the selling price. The second stage involves preparing and posting the withholding tax slip for transportation services rendered to the counterparty. The third stage is drafting the tax return to obtain a Billing ID, which is used for the payment of the payable tax through designated banks or post offices. Once the payment process is completed, PT YTA is automatically considered to have reported its payable Income Tax Article 15 through the Periodic Income Tax Return in the Coretax system. This implementation shows that PT YTA has fulfilled its tax obligations by performing calculation, withholding, payment, and reporting through the Periodic Income Tax Return.